GLOMERULAR FILTRATION RATE AS A MARKER OF KIDNEY DAMAGE IN PATIENTS WITH ARTERIAL HYPERTENSION - P. H. Zelveian; L. G. Dheryan (Евразийский Кардиологический Журнал)
In the recent years there is a tendency for progressive increase in the number of patients with chronic kidney failure (CKF) in the world and, importantly, that this growth does not tend to slow down in the future. Numerous studies have proven a clear relationship between the degree and duration of arterial hypertension (AH) and incidence of CKF. in this view during AH glomerular filtration rate (GFR) reflects early, intermediate and also late stages of kidney damage and in this case changes of GFR have diverse character. so, an increase of absolute values of GFR is typical for early stages of AH and a decrease of GFR is typical for the late stages of AH. in the same time during AH GFR can be presented as a predicting risk factor for other target organ damage and cardiovascular morbidity and mortality development as well. Thus the evaluation of GFR should be more widely introduced in the clinical practice with the purpose of revelation of other cardiovascular risk factors and associated pathological conditions, continuous monitoring and prevention of target organ damage.